PENGARUH LINGKUNGAN KERJA, BEBAN KERJA, KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT DANAMAS INSAN KREASI ANDALAN - Larassati, Alfiyyah; Sugiono; Bhirawa, Sigit Wisnu Setya (Universitas Nusantara PGRI Kediri, 2025)
This study aims to analyze the influence of work environment, workload, and job satisfaction on employee performance at PT Danamas Insan Kreasi Andalan (DIKA) in Kediri Residency. This associative descriptive quantitative research was conducted from April to May 2025, involving 70 PT DIKA employees as both population and sample using a saturated sampling technique. Data was collected via Likert scale questionnaires and analyzed using SPSS 25, including validity, reliability, classical assumption tests, multiple linear regression, and t- and F-tests. The results indicate that work environment and job satisfaction positively and significantly affect employee performance. Workload, however, had a negative but not significant influence. Simultaneously, all three variables significantly impact employee performance. This research highlights the importance of a conducive work environment and job satisfaction for optimizing performance at PT DIKA.